Influence of isotopic composition of silicon on local vibrational modes of vacancy-oxygen complex - Tolkacheva, Ekaterina A.; Markevich, Vladimir P.; Murin, Leonid I. (Journal of the Belarusian State University. Physics, 2021)
Isotopic composition of natural silicon (28Si (92.23 %), 29Si (4.68 %) and 30Si (3.09 %)) affects noticeably the shape of infrared absorption bands related to the oxygen impurity atoms. The positions of local vibrational modes (LVMs), related to quasimolecules 28Si – 16OS – 29Si and 28Si – 16OS – 30Si (OS – substitutional oxygen atom) have been determined for the absorption spectra measured at Т ≅ 20 K and at room temperature (Т ≅ 300 K). An estimation of the isotopic shifts of corresponding modes in a semi empirical way has been done by the fitting the shape of the experimentally measured absorption band related to the vacancy-oxygen center in irradiated Si crystals. The LVM isotope shifts at Т ≅ 300 K are found to be (2.22 ± 0.25) сm–1 for 28Si – 16OS – 29Si and (4.19 ± 0.80) сm–1 for 28Si – 16OS – 30Si in relation to the most intense band with its maximum at (830.29 ± 0.09) cm–1 due to the vibrations of 28Si – 16OS – 28Si, and the full width at half maximum of the A-center absorption bands is (5.30 ± 0.26) cm–1. At Т ≅ 20 K the corresponding values have been determined as (1.51 ± 0.13); (2.92 ± 0.20); (835.78 ± 0.01) and (2.34 ± 0.03) сm–1. A model for the calculation of isotopic shifts in the considered case has been discussed. From an analysis of the observed isotopic shifts some information about the structure of the vacancy-oxygen complex in silicon at Т ≅ 20 K and at room temperature has been obtained.